Midwive’s Attitude in P4K Sticker Installation - Lulut Handayani (Jurnal LINK, 2014)
The study was conducted to determine what factors that associated with the behavior of country midwives in installing P4K sticker in Magelang district. The explanatory research with cross sectional method is used. The population of the study was 362 independent midwives in Magelang. Proporsional Random Sampling was used to take the sample of 80 midwives. The result shows that there is balance amount between the number of midwives who installed the P4K sticker and those who did not, which is 50% or 40 midwives. While the result shows that more than a half (60%) are under 39 years old. 72%of the midwives had diploma III.  60% midwives have worked less than 18 years. 64% midwives considered lack of knowledge, and about 52,5% of midwives have unsupporting attitude. There is a relationship between P4K sticker instalation and midwives’ attitude (P=0,022). The Influence of the installation of the sticker is the midwives’ attitude with OR1 which means that that variable support them to install the P4K sticker.